Analysis of a state of physical education in higher educational establishment. - Klimakova S.N (Kharkov National Pedagogical University, 2011)
Organization of physical training in high schools is insufficiently effective for increase of level of physical readiness, health, motivation and interests of students to employment by physical exercises and sports. Results of questioning about the relation of students to employment by physical training in pedagogical higher educational institutions are presented the reasons of the bad relation of students to employment by physical training are sorted out.